Entrepreneurial leadership style during the Covid-19 pandemic: a systematic literature review - Zhong, Xueyun; Mohd Hizam Hanafiah,; Zaleha Yazid,; Nur Saadah Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The COVID-19 pandemic has underscored the urgent requirement for efficient leadership in both traditional workplaces and entrepreneurial enterprises. Despite previous research suggesting various leadership styles to alleviate work-related stress, limited research has investigated the leadership style adopted by entrepreneurs during the COVID-19 pandemic. This SLR identifies various leadership styles, including open leadership, transformational, transactional, responsible, and inclusive leadership, among others. However, the most appropriate leadership style largely depends on the situation at hand. This study’s systematic literature review followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guideline. It studied data from Scopus and Web of Science from 2020 to 2023. Initially identifying 186 articles, the investigation concluded with 22 articles that provided a full assessment of trends as well as a topic overview. The review found a majority of studies using quantitative methodologies. The review also emphasizes the need for future research to investigate additional characteristics of leadership style, such as the effects of culture, demographic demographics, and organizational decision-making processes on leadership effectiveness. This review provides essential guidance for navigating leadership complexities in entrepreneurship, particularly amidst crises like the COVID-19 pandemic.